Dissolved oxygen shapes the archaeal communities in the seawater of Changjiang Estuary - Wang, Jianxin; Tian, Chunmiao; Wu, Dongmei; Wang, Rixin (Frontiers in Environmental Science, 2023)
Archaea play a significant role in regulating the biogeochemical processes of marine systems. In this study, high-throughput sequencing was used to examine the archaeal community in the hypoxic and non-hypoxic zones of the Changjiang Estuary. Thaumarchaeota (formerly Marine Group (MG) I) dominated the hypoxic zones (bottom waters), and Euryarchaeota were mainly distributed in the non-hypoxic zones (surface waters). These results indicate that the two zones had distinct archaeal community structures. Moreover, Thaumarchaeota and Nitrosopumilales were positively correlated with salinity, but negatively correlated with DO and temperature. Temperature, PO43-, and DO had a significant correlation with archaeal richness, while NH4+correlated with archaeal diversity. A network analysis revealed that the same species (MG II) may play distinct roles in both hypoxic and non-hypoxic zones. Therefore, the hypoxic and non-hypoxic habitats differ greatly in their archaeal community structures.